Analisis Faktor Perlindungan Konsumen Dalam Urgensi Pembentukan Undang-Undang Pinjaman Online (Peer To Peer Lending) - Helena Toshely Sasmita; Suci Kamilah; Rina Irsni Wardodo; Thody Daniel Satya Wira Wicaksana (Universitas Airlangga, 2022)
AbstractFinancial Technology (Fintech) is currently developing in Indonesia. This is due to the development of increasingly advanced and sophisticated technology and the presence of fintech types of peer-to-peer lending that offer loans easily and quickly. The purpose of this study is to examine and analyze consumer protection factors in the urgency of establishing an online lending law (peer-to-peer lending). This type of research uses normative legal research methods, with a statutory approach and a conceptual approach. Various problems in the use of online loan services (fintech), including in terms of interest rate transparency, misuse of consumer personal data by lending companies, and collection methods that are not following legal rules, while in Indonesia the legal basis for online loan services is only accommodated by POJK No. 77/POJK.01/2016 which has not been able to fully accommodate all aspects of consumer protection such as the mechanism for monitoring online loan services, guarantees for consumer protection for the use of online loan services, and regulations regarding operating permits for fintech peer to peer lending. With the establishment of the online loan law, it is hoped that it will provide legal certainty for consumers in using online loan services today.Keywords: Consumer Protection; Constitution; Financial Technology.AbstrakFinancial Technology (Fintech) saat ini sedang berkembang di indonesia. Hal ini dikarenakan perkembangan teknologi yang semakin maju dan canggih serta kehadiran fintech jenis peer to peer lendingyang menawarkan pinjaman dengan mudah dan cepat. Tujuan penelitian ini adalah untuk mengkaji dan menganalisis faktor-faktor perlindungan konsumen dalam urgensi pembentukan undang-undang pinjaman online (peer to peer lending). Jenis Penelitian ini menggunakan metode penelitian hukum normatif, dengan pendekatan peraturan perundang-undangan (statute approach) dan pendekatan konseptual (conseptual approach). Berbagai permasalahan dalam penggunaan layanan pinjaman online (fintech) diantaranya adalah dari segi transparasi suku bunga, penyalahgunaan data pribadi konsumen oleh perusahaan pemberi pinjaman serta cara penagihan yang tidak sesuai dengan aturan hukum, sedangkan di Indonesia dasar hukum layanan pinjaman online hanya diakomodasi oleh POJK No. 77/POJK.01/2016 yang belum dapat sepenuhnya mengakomodasi seluruh sisi perlindungan konsumen seperti mekanisme pengawasan layanan pinjaman online, jaminan perlindungan konsumen atas penggunaan layanan pinjaman online dan aturan mengenai izin operasi fintech peer to peer lending. Dengan dibentuknya Undang – Undang pinjaman online diharapkan dapat memberikan kepastian hukum bagi konsumen dalam penggunaan layanan pinjaman online saat ini.Kata Kunci: Perlindungan Konsumen; Undang-Undang; Fintech.